2014
DOI: 10.1038/srep03774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Receptive Joint Attention in Chimpanzees (Pan troglodytes)

Abstract: Despite their genetic similarity to humans, our understanding of the role of genes on cognitive traits in chimpanzees remains virtually unexplored. Here, we examined the relationship between genetic variation in the arginine vasopressin V1a receptor gene (AVPR1A) and social cognition in chimpanzees. Studies have shown that chimpanzees are polymorphic for a deletion in a sequence in the 5′ flanking region of the AVPR1A, DupB, which contains the variable RS3 repetitive element, which has been associated with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 61 publications
(89 reference statements)
6
63
0
Order By: Relevance
“…In line with this, experimental testing in male chimpanzees has shown that individuals with a DupB+ allele are more responsive to socio-communicative cues of humans compared to males homozygous for the DupB deletion31. Bonobos are also known to outperform chimpanzees in tasks related to theory of mind43 and are better at gaze-following44.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In line with this, experimental testing in male chimpanzees has shown that individuals with a DupB+ allele are more responsive to socio-communicative cues of humans compared to males homozygous for the DupB deletion31. Bonobos are also known to outperform chimpanzees in tasks related to theory of mind43 and are better at gaze-following44.…”
Section: Discussionmentioning
confidence: 80%
“…Chimpanzees with a DupB+ allele were rated higher on Conscientiousness but lower on Extraversion16, and DupB+ males scored higher on Conscientiousness and Dominance than females30. Finally, the DupB deletion was associated with a reduction in attentiveness to human social cues31.…”
mentioning
confidence: 92%
“…Presumably these attributes would have conferred advantages to some individuals potentially in the way of enhanced foraging skills or increase social skills, leading to increased opportunities for access to food or mating [24, 25]. These individuals would have then potentially had increased survival and fitness, traits that would have become increasingly selected upon during primate evolution, as has been postulated by a number of theorist going all the way back to Darwin [26-30].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the chimpanzees in each colony are related and this allowed for an analysis of heritability in tool use and asymmetry using quantitative genetics based on the entire pedigree (table 1). Consistent with approaches used by others [48][49][50][51][52][53][54][55][56], to estimate heritability, we used the software package SOLAR [57]. SOLAR uses a variance components approach to estimate the polygenic component of variance when considering the entire pedigree (see [48,51,54]).…”
Section: (D) Data Analysismentioning
confidence: 99%